Unsafe actions and unsafe conditions in cement production workers: A Cross Sectional Study - Basri, Syahrul; Pirmah, Nurul Anisa (Universitas Islam Negeri Alauddin Makassar, 2023)
Occupational accidents are all unplanned events that cause or have the potential to cause injury, illness, damage or other losses, both for workers and for the company. This study aims to determine the factors associated with work accidents in Cement Production workers at PT. Cement Bosowa Maros. The type of research used is quantitative with an analytic observational approach using a cross sectional design. The population in this study are cement production workers at PT. Semen Bosowa Maros with a total sampling technique of 86 people. The results showed that the variables related to work accidents were unsafe action (p-value=0.032), unsafe condition (p-value=0.002). While the unrelated variables are age (p-value = 0.244), and length of work (p-value = 1000). It is recommended to the company PT. Semen Bosowa Maros is advised to ensure that workers use proper and correct personal protective equipment while working, and conduct OHS training so that workers understand more about safe behavior and conditions so that work accidents do not occur due to unsafe behavior and conditions. And ensure a safe and comfortable work environment for workers.